Political Instability and Impact on Nepal’s Tax Revenue Collection - Kafle, Pabitra (Ganeshman Darpan, 2026)
This study examines the impact of political instability on Nepal’s tax revenue collection and its broader effects on the national economy. The main objective of the study is to explore how political instability has influenced tax collection practices and economic policy implementation in Nepal. The study adopted a qualitative research design based on descriptive methodology to understand the socio-political and economic realities surrounding the taxation system. Secondary data were collected from the official website to analyze trends in tax revenue collection over recent fiscal years. The findings reveal that tax revenue collection during the past five fiscal years was a noticeable fluctuation. Frequent political changes, unstable governance, policy inconsistency, and weak administrative coordination negatively affected the efficiency of tax administration and compliance. The study further found that political instability has adversely impacted Nepal’s overall economic system by reducing public investment in critical sectors such as education, healthcare, infrastructure development, agricultural modernization, and sustainable development programs. As a result, economic growth and public service delivery have been significantly constrained. The study concludes that political stability, transparent governance, and effective fiscal policies are essential for strengthening Nepal’s tax system and promoting long-term economic development.